Ordered Completion for First-Order Logic Programs on Finite Structures - Asuncion, Vernon; Lin, Fangzhen; Zhang, Yan; Zhou, Yi (Proceedings of the AAAI Conference on Artificial Intelligence, 2010)
In this paper, we propose a translation from normal first-order logic programs under the answer set semantics to first-order theories on finite structures. Specifically, we introduce ordered completions which are modifications of Clark's completions with some extra predicates added to keep track of the derivation order, and show that on finite structures, classical models of the ordered-completion of a normal logic program correspond exactly to the answer sets (stable models) of the logic program.